Performance of phase contrast angiography in quantifying valvular regurgitation: an in-vitro model - Fox, James F.; Doyle, Mark W.; Anayiotos, Andreas (My University, 1995)
The proximal flowfield is the most promising region of interest in quantifying valvular regurgitation. The proximal isovelocity surface area (PISA) method has become the standard in attempting to quantify valvular regurgitation within this region. Current in-vivo techniques, including color Doppler ultrasound (CDU), quantify flow but fail to obtain directly the shape of the isovelocity contour due to instrumentation limitations. An approach to quantifying valvular regurgitation using magnetic resonance imaging (MRI) is presented here. MR phase contrast angiography (PCA) provides a wealth of three-dimensional spatial and velocity information. From the data obtained, true shapes of isovelocity surfaces emerge, eliminating the need for extrapolation. Using an in vitro model, this investigation intends to show the robustness of PCA in assessing valvular regurgitation and directly quantifying flow.
Keywords: Biomechanics; Flow meters; Magnetic resonance imaging; Angiography